Tingkat Prokrastinasi Akademik Siswa di Masa Pandemi Covid-19 - Gracelyta, Theadora; Harlina, Harlina (Jurnal Konseling Komprehensif: Kajian Teori dan Praktik Bimbingan dan Konseling, 2021)
The education sector has been influenced the spread of the Covid-19 virus which almost all schools were to prevent the Covid-19 virus. This study aims to determine the level of academic procrastination of class XI students of SMA Negeri 1 Martapura. This study uses aquantitative descriptive method. The data collected using the psychological scale of academic procrastination Likert scale model. The number of samples selected as many as 161 students from class XI was selected randomly by using proportional random sampling technique. The data analysis technique used is the percentage (%). The results showed that academic procrastination which includes four aspects, namely time perception, action intention, emotional stress, and perceptual ability is in the moderate category with a percentage of 63.35%. In the low category with a percentage of 32.30% and the high category with a percentage of 4.35%. So it can be said that all respondents show the level of academic procrastination is in the category with a percentage of 63.35%.